Geraniin supplementation increases human keratinocyte proliferation in serum-free culture - Indra Kusuma; Restu Syamsul Hadi (Universa Medicina, 2013)
BACKGROUND Various products used in cellular therapy utilize tissue culture techniques requiring keratinocyte culture. An efficient and clinically acceptable keratinocyte culture system requires supplements with mitogenic activity. Geraniin is a phytochemical with the potential as a supplement for expansion culture of keratinocytes. The objective of the present study was to verify the mitogenic activity of geraniin on human keratinocytes. METHODS This was an experimental study using two samples of human foreskin obtained by circumcision of a male child. Epidermal keratinocytes were isolated from the foreskin samples and were divided into paired groups, comprising intervention and control groups. The intervention groups were cultured with geraniin supplementation, whereas the control groups with standard supplements, without the addition of geraniin. Mitochondrial activity of the cells was evaluated by means of the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl-tetrazolium-bromide (MTT) proliferation assay. Absorbance values in each of the groups was measured at 450 nm. Data analysis was performed with the paired t-test. RESULTS Geraniin supplementation significantly increased the keratinocyte proliferation rates at dosages of 0.8 to 3.1 μM. An increase of 57% in the proliferation rate was obtained at a dosage of 1.6 μM, while at a dosage of 12.5 μM toxic effects were starting to appear. Geraniin presumably causes increased cellular energy status, resulting in increased proliferation rates. CONCLUSION The findings in this study provide evidence in support of the utilization of geraniin as a supplement for expansion culture of keratinocytes. Further studies may presumably identify the molecules acting as geraniin receptors and the intracellular mechanisms underlying the increase in proliferation rates.